Snow Lion - McPhail, David; Nang Chan Yeema (New York, USA Parents Magazine Press, 1982)
Lion, finding the jungle too hot for comfort, visits the mountains and falls in love with the cold fluffy white snow that covers the ground there.
Keywords: Story Collection